Weight-related and analytical maternal factors in gestational diabetes to predict birth weight and cord markers of diabetic fetopathy. (2nd July 2016) - Garcia-Flores, Jose; Cruceyra, Mireia; Cañamares, Marina; Garicano, Ainhoa; Nieto, Olga; Espada, Mercedes; Lopez, Ana; Tamarit, Ines; Sainz De La Cuesta, Ricardo
Abstract: Objective : The objective was to determine the value of clinical and analytical maternal factors to predict birth weight and umbilical cord biochemical markers of diabetic fetopathy. Methods : Prospective evaluation of gestational diabetes pregnancies ( n  = 50). Maternal weight-related clinical and analytical factors were collected during pregnancy. After birth, an umbilical cord sample was taken. Results : Univariate linear regression analysis showed relationship between maternal weight, glycated hemoglobin (HbA1c) and insulin-like growth factor 1 (IGF1) with birth weight percentile. A significant association was found between maternal weight and cord insulin and C-peptide. Maternal HbA1c, leptin and insulin during pregnancy showed a positive linear association to cord leptin, insulin and C-peptide. In multivariate analysis models, final maternal BMI showed an independent positive association with cord C-peptide. Conclusions : Maternal weight-related and analytical parameters show diagnostic value to birth weight and cord markers.